2020
DOI: 10.3947/ic.2020.52.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 Fatty Acids and COVID-19: A Comprehensive Review

Abstract: The rapid international spread of severe acute respiratory syndrome coronavirus 2 responsible for coronavirus disease 2019 (COVID-19) has posed a global health emergency in 2020. It has affected over 52 million people and led to over 1.29 million deaths worldwide, as of November 13th, 2020. Patients diagnosed with COVID-19 present with symptoms ranging from none to severe and include fever, shortness of breath, dry cough, anosmia, and gastrointestinal abnormalities. Severe complications are largely due to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 63 publications
1
96
0
6
Order By: Relevance
“…It was demonstrated that fish oil increased antiviral response and inhibited virus replication [ 44 ]. It is possible that the increased dietary omega-3 consumption or its supplementation may promote the prophylaxis and treatment of COVID-19 via the reduction of the intensity of the inflammation (COVID-19) [ 45 ]. Therefore, omega-3 acids may exert a positive effect on inflammatory diseases [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that fish oil increased antiviral response and inhibited virus replication [ 44 ]. It is possible that the increased dietary omega-3 consumption or its supplementation may promote the prophylaxis and treatment of COVID-19 via the reduction of the intensity of the inflammation (COVID-19) [ 45 ]. Therefore, omega-3 acids may exert a positive effect on inflammatory diseases [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been fairly extensive discussion about the contradictory actions of ACE2 in viral entry to host cells and its regulation of the RAS where modulation of RAS has a positive pathological effect. The ACE2 receptor is expressed in lung tissues, and a range of other tissues such as nose, heart, endothelium, kidney and intestine [ 131 , 132 ]. It has now been resolved that once the virus binds to ACE2, it effectively removes it from further action, promoting ACE activity which in turn leads to production of more Ang II.…”
Section: Covid-19mentioning
confidence: 99%
“…Additionally, one of the major causes of death in patients infected with SARS during COVID-19 is multiorgan failure, which is a result of immune system overdrive causing cytokine storms. The Omega-3 FA is known to produce less pro-inflammatory cytokines, therefore increasing Omega-3 FA intake in the diet or supplementation could decrease viral entry, promote better immune function, and decrease severity among those who have been diagnosed with COVID-19 [24].…”
Section: Pros and Cons Of Pufas In Covid-19 Diseasementioning
confidence: 99%